The Model of the Internal Monitoring Unit After the Determination of IAIN to Become a UIN - Erwin, Erwin; Misneli, Misneli; Nasfi , Nasfi (International Journal of Social and Management Studies, 2022)
The Internal Supervisory Unit (SPI) at State Islamic Religious Universities (PTKIN) carries out supervisory duties in accordance with the Minister of Religion Regulation of the Republic of Indonesia No. 25 of 2017. SPI as one of the supervisory system tools, is required to focus on achieving governance, control, risk management, not just just administrative work. The existence of SPI at PTKIN must be understood by elements within the organization and have the same perception regarding the scope of the audit area by the organization and top management. This study uses the "A Case Study" method or case study. Research data through interview techniques, observation and documentation. The data is processed through the stages of data processing, checking the correctness of the data, compiling data, carrying out coding, classifying data, correcting unclear interview answers. This stage is carried out to facilitate the analysis stage and research conclusions. From the results of this study it was found that the implementation of internal control at PTKIN has been running but has not covered all aspects of supervision, the efforts made to increase supervision include increasing the number of personnel and supporting tools such as an integrated information system. The SPI performance system must be able to cover all aspects of activities in the work unit so that the supervision system runs at PTKIN